Description of Academic Self-Efficacy Of "X" Sidoarjo High School Students - Agung Kurniawan; Ghozali Rusyid Affandi (Inquest Journal, 2022)
This research is motivated by a decrease in academic self-efficacy possessed by students. The purpose of this study was to find out and provide an explanation of the description of academic self-efficacy in high school students "X" Sidoarjo. This research method is descriptive and quantitative with number of subjects as many as 167 students. Determination of subjects using proportionate stratified random sampling technique, namely taking samples from members of the population randomly and proportionally stratified. The variable in this study is academic self-efficacy. Data collection in this study used a psychological preparation scale, namely the Likert scale for academic self-efficacy variables. Analysis of the data in this study using SPSS 26.0 for Windows and Excel. The results of data analysis showed that the academic self-efficacy of SMA "X" Sidoarjo students was in the medium category with a percentage of 75%, a small portion of academic self-efficacy was low with a percentage of 12% and a small portion also had high academic self-efficacy with a percentage of 12%.